Identification of a unique anti-Ro60 subset with restricted serological and molecular profiles. (17th September 2020) - Lee, A Y S; Beroukas, D; Brown, L; Lucchesi, C; Kaur, A; Gyedu, L; Hughes, N; Ng, Y H; Saran, O; Gordon, T P; Wang, J J
Summary: Anti-Ro60 is one of the most common and clinically important serum autoantibodies that has a number of diagnostic and predictive capabilities. Most diagnostic laboratories report this simply as a qualitative positive/negative result. The objective of this study was to examine the clinical and serological relevance of a novel subset of anti-Ro60 in patients who display low levels of anti-Ro60 (anti-Ro60 low ). We retrospectively identified anti-Ro60 sera during a 12-month period at a major immunopathology diagnostic laboratory in Australia. These all were anti-Ro60-precipitin-positive on the diagnostic gold standard counter-immuno-electrophoresis (CIEP). Lineblot immunoassay was used to stratify patients into either anti-Ro60 low or anti-Ro60 high subsets. We compared the medical and laboratory parameters associated with each group. Enzyme-linked immunosorbent assay (ELISA) and mass spectrometry techniques were used to analyse the serological and molecular basis behind the two subsets. Anti-Ro60 low patients displayed less serological activity than anti-Ro60 high patients with less intermolecular spreading, hypergammaglobulinaemia and less tendency to undergo anti-Ro60 isotype-switching than anti-Ro60 high patients. Mass spectrometric typing of the anti-Ro60 low subset showed restricted variable heavy chain subfamily usage and amino acid point mutations. This subset also displayed clinical relevance, being present in a number of patients with systemic autoimmune rheumatic diseases (SARD). We identify a novel anti-Ro60 low patient subset that is distinct from anti-Ro60 high patients serologically and molecularly. It is not clear whether they arise from common or separate origins; however, they probably have different developmental pathways to account for the stark difference in immunological maturity. We hence demonstrate significance to anti-Ro60 low and justify accurate detection in the diagnostic laboratory. Graphical Abstract: